Foreign psychology studies of envy: a breef overview on main approaches and perspectives of studying in a cross-cultural aspect - Matusevich E.V.; Kochetova T.V. (Современная зарубежная психология, 2018)
In this article envy is considered as a complex psychological phenomenon that has a structure and at least four aspects of which can be represented in a study: dynamic, pithful, structural and cross-cultural. It is emphasized that the main mechanism of the actualization of this psychological phenomenon is social comparison, as a result of which the subject feels and realizes his or someone else's superiority. Person can be fully aware of envy, but, at an unconscious level, it can, as a basis of the activity motives, provoke him to act. Forms of experiencing envy as a feeling are individual, they can change and transform over time, depending on what is valuable to the person at the moment. At the same time, envy is an unavoidable element of the social life of a person; it can perform an important function in the adaptation of a person in society.